Maternal genome-wide DNA methylation profiling in gestational diabetes shows distinctive disease-associated changes relative to matched healthy pregnancies. Issue 2 (1st February 2018) - Wu, Pensee; Farrell, William E.; Haworth, Kim E.; Emes, Richard D.; Kitchen, Mark O.; Glossop, John R.; Hanna, Fahmy W.; Fryer, Anthony A.
ABSTRACT: Several recent reports have described associations between gestational diabetes (GDM) and changes to the epigenomic landscape where the DNA samples were derived from either cord or placental sources. We employed genome-wide 450K array analysis to determine changes to the epigenome in a unique cohort of maternal blood DNA from 11 pregnant women prior to GDM development relative to matched controls. Hierarchical clustering segregated the samples into 2 distinct clusters comprising GDM and healthy pregnancies. Screening identified 100 CpGs with a mean β-value difference of ≥0.2 between cases and controls. Using stringent criteria, 5 CpGs (within COPS8, PIK3R5, HAAO, CCDC124, and C5orf34 genes) demonstrated potentials to be clinical biomarkers as revealed by differential methylation in 8 of 11 women who developed GDM relative to matched controls. We identified, for the first time, maternal methylation changes prior to the onset of GDM that may prove useful as biomarkers for early therapeutic intervention.